EDUKASI DAN PELATIHAN PROGRAM PENGELOLAAN SAMPAH (PPS) DAN KONTRIBUSINYA DALAM CAPAIAN SUSTAINABLE DEVELOPMENT GOALS (SDGS) - Kafabih, An’im; Destiartono, Mohamad Egi (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2024)
Sustainable development is a pivotal agenda that must be enforced by each region in Indonesia. This community service article aims to investigate the problems of waste management in Banglarangan Village, Ampelgading District, as well as attempts to offer related programs to tackle those issues. The methods applied were field observations, in-depth interviews, and literature studies. The results of field observations and interviews found that Banglarangan Village has several waste management problems, namely (i) sustainable waste management has not been implemented by the majority of the Community Association (RT); (ii) Those RTs have conducted traditional waste management; and (iii) public awareness on waste management is still low. Following these findings, we offer several programs, i.e., waste banks and paving blocks for an-organic wastes, as well as co-enzymes for organic wastes.